The impact of educational units on student achievement of art history in the Department of Art Education (Journal of the College of Basic Education, 2022)
Check researcher on a lot of theories and models of teaching, and found that the modules if formulated within Merle theory characterized from others in terms of matching steps with the philosophy of teaching modern art education in terms of the educational environment and the diversification of activities and focus on the learner and the positive activity in the light of the teaching methods and educational activities learning design. The goal of current research to 1-building educationa unit designed according to the model Merle prescribed in the Departme of Art Education - College of Basic Education - Mustansiriya University. 2-effective module through applied to the students of the first phase -lam school 2013-2014 - second semester - the morning of the study. To achieve the goal of this research scholar coined the null hypothesis of the following: There were no statistically significant differences at the level of (0.05) Between the average grades students of the experimental group and the control group in the answer to paragraphs achievement test cognitive Uday.Chose researcher sample Find a way random clouds and consisted of 70 students, divided between two rooms, seminars, by (35) students, the researcher relied on one of the experimental designs of the two groups Almtkavitan (experimental and control) is a post-test, because it is appropriate to target research and hypothesis. Rewarded with two sets Search variables (chronological age of the students measured in months, the pre-test scores "prior knowledge test in art history"), a promising researcher modules designed according Merle) model, which includes ten lessons, as coined paragraphs (achievement test) of the type multiple choice with four alternatives, has been verified validity and reliability, and the difficulty and expense of discriminatory power and effectiveness of false alternatives to testing laboratories. After application of the experiment and collect data, were processed statistically using samples t-test (t - Test) for two independent samples to address Albeanat.ccant Find outweigh the experimental group that studied loneliness educational designed according Merle model in the teaching of art history at the control group which studied according to the method result normal "lecture" in art history. Accordingly, the researcher recommended: 1-adoption of the model Merle in the teaching of art history because it has proven effective in the formation of the experiences and attitudes about the positives of knowledge content. 2- Rewriting content and building knowledge of the content of art history line with the evolution of educational institutions. 3-interest in modern ways of teaching that makes the learner axis of the learning process.